A high-emissivity aerogel thermal insulation coating based on dynamic covalent bond pore protection and phonon resonance and a preparation method thereof

CN122978799APending Publication Date: 2026-10-27CHINA CONSTR EIGHT ENG DIV CORP LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610892021.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-18
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

[0009]针对现有气凝胶涂料中树脂侵入导致导热系数升高与低树脂含量导致粘结强度不足的矛盾,以及现有涂料在红外大气窗口发射率难以突破98%的技术瓶颈,本发明提供一种基于动态共价键护孔与声子共振的高发射率气凝胶绝热涂料,该高发射率气凝胶绝热涂料导热系数极低、粘结强度极高,同时具备卓越的太阳光反射比、近红外光反射比以及超高垂直发射率,可有效克服现有技术所存在的问题

Benefits of technology

1、本发明通过“顺二醇基树脂”与“苯硼酸修饰气凝胶”的锁钥匹配设计,在涂料成膜的瞬间,于气凝胶孔口处原位生成动态硼酸酯交联网络。该网络作为一种动力学分子闸门,彻底阻止了树脂分子向气凝胶纳米孔洞内部的毛细渗透,使气凝胶的绝热结构得以完美保留。同时,该动态共价键提供了强大的界面结合力,使得涂层在极低树脂用量下,仍能实现≥1MPa的超高粘结强度。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The application discloses a kind of high-emissivity aerogel heat insulation coating based on dynamic covalent bond hole protection and phonon resonance and preparation method thereof, comprising by mass percentage: cis-diol group modified fluorosilicone resin 15~30%;Benzene boric acid modified hollow BaSO4@SiO2aerogel microspheres 20~40%;Praseodymium-doped strontium titanate 5~15%;Fluorinated graphene quantum dots 2~8%;Auxiliary agent 2~5%;The balance is water.The application initiates dynamic covalent bond in-situ hole sealing mechanism, utilizes borate ester bond in aerogel interface instant crosslinking, completely blocks resin infiltration nanometer pore, while guaranteeing bonding strength ≥1MPa, reduces thermal conductivity to ≤0.04W / (m·K).Meanwhile, utilize the broadband phonon resonance synergistic effect between multistage components, realize solar light and near-infrared light reflectance ≥0.9, vertical emissivity is as high as ≥98%.The application has great application potential in building energy saving, industrial pipeline heat insulation, aerospace thermal protection field.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of functional coatings technology, and in particular to an aerogel insulating coating with ultra-low thermal conductivity, high mechanical strength and extreme radiative cooling performance, and its preparation method. Background Technology

[0002] Among all energy-saving methods, using coatings that combine heat reflection and insulation to provide thermal protection for building exteriors, storage tanks, pipelines, etc., is widely recognized as the most economical and easiest-to-implement technical approach.

[0003] Traditional thermal insulation coatings mainly rely on adding low thermal conductivity fillers such as hollow glass microspheres and ceramic microspheres. However, the internal cavities of these fillers are on the micrometer scale, and convective heat transfer still occurs within the internal gas, resulting in an overall thermal conductivity of the coating typically between 0.06 and 0.10 W / (m·K), indicating a clear physical ceiling to its insulation performance. Silica aerogel, as the solid material with the lowest known thermal conductivity (as low as 0.012–0.018 W / (m·K) at room temperature), possesses a unique three-dimensional nano-network structure that effectively restricts the free path of air molecules, thereby eliminating convective heat transfer. Therefore, incorporating aerogels into coating systems to prepare aerogel thermal insulation coatings has become a research hotspot in recent years.

[0004] However, despite the excellent properties of aerogel materials, existing aerogel coatings have encountered a world-class technical bottleneck in practical applications that has not yet been fundamentally resolved—the paradox of the contradiction between thermal insulation performance and mechanical strength.

[0005] Specifically, aerogel powder itself lacks adhesive properties and must be bonded to the substrate by a polymeric film-forming resin (such as acrylic, polyurethane, epoxy resin, etc.). However, during the liquid curing process of the coating, resin molecules, under the influence of strong capillary forces, inevitably penetrate and fill the nanopores inside the aerogel. This resin intrusion completely destroys the nanoporous structure that aerogel is so proud of, replacing the air with highly thermally conductive solid resin (the thermal conductivity of resin is typically around 0.2 W / (m·K)). As a result, even with the addition of a large amount of expensive aerogel, the actual thermal conductivity of the final coating often remains as high as 0.05~0.08 W / (m·K), defeating the original purpose of using aerogel.

[0006] To prevent resin from seeping into the pores, the current conventional approach is to drastically reduce the amount of resin added or to use a hydrophobic agent for a rough surface treatment of the aerogel. However, this directly leads to a sharp drop in the adhesion strength of the coating. When the resin content is too low, the coating cannot form a continuous, dense film, resulting in severe powdering and peeling. The adhesion strength to the substrate is usually less than 0.5 MPa, which is far from meeting the national standards for outdoor wind pressure resistance or industrial anti-peeling (≥1.0 MPa). It can be said that the current system can only passively compromise between pore preservation (thermal insulation) and film formation (high strength), and cannot achieve both simultaneously.

[0007] On the other hand, modern thermal insulation coatings, in addition to blocking heat conduction, also need to possess excellent passive radiative cooling capabilities, that is, to emit the absorbed heat into the absolute zero (3K) outer space at specific wavelengths (mainly concentrated in the 8-13μm atmospheric infrared window). Conventional reflective thermal insulation coatings typically use rutile titanium dioxide (TiO2) as a reflective filler. However, TiO2 exhibits strong intrinsic absorption in the ultraviolet band, and its reflectivity in the near-infrared band (0.78-2.5μm) decreases rapidly with increasing wavelength. More critically, the infrared emissivity (vertical emissivity) of conventional polymers and fillers in the 8-13μm band is typically only around 0.85-0.90. According to the Stefan-Boltzmann law, for every 1% increase in emissivity, the radiative heat dissipation power increases significantly. When the target is polar cooling or extreme thermal insulation under high-intensity direct sunlight, an emissivity of 0.90 is far from sufficient. In the scientific community, breaking the limitations of phonon vibration frequency in materials and increasing the vertical emissivity of coatings to near the theoretical limit of blackbody (≥98%), while also taking into account solar and near-infrared reflectance of over 0.9, is a highly challenging and cutting-edge interdisciplinary research topic.

[0008] In summary, existing aerogel coating technologies suffer from two fundamental flaws: first, the lack of an interface protection mechanism that can provide both superior adhesion and precise prevention of resin damage to aerogel pores; and second, the lack of material synergy design capable of achieving both strong full-spectrum reflection and ultra-high radiation in the limiting wavelength range. Therefore, there is an urgent need to develop a novel, original, and innovative aerogel insulation coating to break through existing technological barriers. Summary of the Invention

[0009] To address the contradiction between the increased thermal conductivity caused by resin intrusion and insufficient bonding strength due to low resin content in existing aerogel coatings, as well as the technical bottleneck that existing coatings struggle to exceed 98% emissivity in the infrared atmospheric window, this invention provides a high-emissivity aerogel thermal insulation coating based on dynamic covalent bond pores and phonon resonance. This high-emissivity aerogel thermal insulation coating has extremely low thermal conductivity, extremely high bonding strength, and also possesses excellent solar reflectance, near-infrared reflectance, and ultra-high vertical emissivity, effectively overcoming the problems existing in the prior art.

[0010] To achieve the above objectives, the present invention provides the following technical solution: Option 1: This invention first provides a high emissivity aerogel thermal insulation coating based on dynamic covalent bond pores and phonon resonance, which is composed of the following components by mass percentage: Component A: Cis-diol-modified fluorosilicone resin aqueous dispersion, 15-30%; Component B: Hollow BaSO4@SiO2 aerogel microspheres modified with phenylboronic acid, 20-40%; Component C: Praseodymium-doped strontium titanate (Pr-SrTiO3) micro powder, 5-15%; Component D: Fluorinated graphene quantum dots (F-GQDs), 2-8%; Component E: Additives, 2-5%; Component F: Deionized water, replenished to 100%.

[0011] Furthermore, the cis-diol-modified fluorosilicone resin is a polymeric film-forming base material prepared by hydrosilylation and free radical copolymerization of hydrogen-containing silicone oil, fluorinated acrylate, and an allyl compound containing cis-diol groups. The cis-diol groups are glycerol monoallyl ether residues.

[0012] Furthermore, the phenylboronic acid-modified hollow BaSO4@SiO2 aerogel microspheres have a core-shell structure, with a core of hollow barium sulfate (BaSO4) microspheres and a shell of silica aerogel layer, the thickness of which is 50 to 100 nm; the outer surface of the aerogel layer is covalently grafted with p-carboxyphenylboronic acid molecules, and the grafting rate is not less than 5 wt%.

[0013] Furthermore, in the praseodymium-doped strontium titanate micropowder, the molar ratio of praseodymium (Pr) is 2 to 5 mol%, and its particle size is 200 to 500 nm.

[0014] Furthermore, the characteristic absorption peak of the fluorine-carbon bond (CF) in the fluorinated graphene quantum dots (F-GQDs) is located between 1100 and 1300 cm⁻¹. -1 .

[0015] Furthermore, the additives include pH adjusters, dispersants, leveling agents, and defoamers; the pH adjuster is 2-amino-2-methyl-1-propanol (AMP-95), used to adjust the pH of the coating system to a weakly alkaline range of 8.5 to 9.5.

[0016] Option 2: This invention also provides a method for preparing the aerogel thermal insulation coating, comprising the following steps: (1) Mix measured amounts of deionized water, dispersant and fluorinated graphene quantum dots, and perform ultrasonic dispersion treatment to obtain a uniform base liquid; (2) Add praseodymium-doped strontium titanate micro powder to the base liquid obtained in step (1) and perform high-speed shear dispersion to obtain a dispersion slurry; (3) Add cis-diol-modified fluorosilicone resin aqueous dispersion to the dispersion slurry obtained in step (2) and stir until homogeneous; (4) Add phenylboronic acid-modified hollow BaSO4@SiO2 aerogel microspheres slowly in batches to the mixture obtained in step (3) under low shear stirring conditions, and mix evenly; (5) Add a pH adjuster to the mixture obtained in step (4) to adjust the pH value of the system to a weakly alkaline range of 8.5 to 9.5, then add a leveling agent and a defoamer, and then perform vacuum degassing treatment to obtain the aerogel thermal insulation coating.

[0017] Furthermore, the low shear force stirring conditions described in step (4), with a stirring speed of 30 to 60 r / min, are used to prevent the core-shell structure of the aerogel microspheres from being mechanically damaged during the mixing process.

[0018] Compared with the prior art, the beneficial effects of the present invention are: 1. This invention utilizes a key-lock design between "cis-diol-based resin" and "phenylboronic acid-modified aerogel" to generate a dynamic borate ester crosslinking network in situ at the aerogel pores during coating film formation. This network acts as a kinetic molecular gate, completely preventing resin molecules from capillary penetration into the aerogel nanopores, thus perfectly preserving the aerogel's insulating structure. Simultaneously, this dynamic covalent bond provides strong interfacial bonding, enabling the coating to achieve an ultra-high adhesion strength of ≥1 MPa even with extremely low resin content.

[0019] 2. This invention constructs a broadband phonon resonance system covering the 8 to 13 μm atmospheric infrared window through precise spectral matching of multiple components: aerogel SiO2, fluorinated graphene quantum dots, strontium titanate, and fluorosilicone resin. This system utilizes the superposition of phonon vibration absorption peaks from the characteristic chemical bonds and lattice of each component to achieve maximal absorption and emission of infrared radiation in this band, resulting in a vertical emissivity of the coating of ≥98%, significantly exceeding the performance limits of existing high-emissivity coatings.

[0020] 3. This invention uses hollow BaSO4@SiO2 aerogel microspheres instead of traditional TiO2, working synergistically with Pr-SrTiO3. The hollow core-shell structure provides multiple refractive index interfaces, enhancing Mie scattering across the entire wavelength range; Pr doping, by widening the bandgap and introducing localized surface plasmon resonance, strengthens reflection in the near-infrared band. This combination enables the coating to achieve a solar reflectance and near-infrared reflectance of ≥0.9, realizing highly efficient solar reflection across the entire wavelength range. Detailed Implementation

[0021] To make the technical means, creative features, objectives and effects of this invention easier to understand, the invention will be further explained below with reference to specific examples.

[0022] This invention utilizes a synergistic design of interfacial chemical kinetics and solid-state spectroscopy to construct two core functional mechanisms within the coating, thereby addressing the two fundamental deficiencies mentioned in the background art: Traditional hydrophobic surface treatments only reduce surface tension. According to the Laplace equation, when the capillary pore size is extremely small (such as the 20nm mesopores of aerogel), even with a large contact angle, capillary pressure is still sufficient to force low molecular weight resin to penetrate. This invention completely abandons the thermodynamic approach to impermeability and instead adopts a kinetic blocking mechanism. The designed polymer system exhibits spatial and temporal adaptability: cis-glycol-modified fluorosilicone resin in water has excellent flowability (low viscosity); however, at the instant the water evaporates and the resin front contacts the aerogel particle surface, the pH=9.0 microenvironment maintained by AMP-95 triggers a dehydration condensation reaction, generating borate ester bonds. The rate constant of this reaction is much greater than the fluid permeation rate within the capillary pores. As a result, the resin instantaneously solidifies at the aerogel pore entrance, forming a dynamic molecular gate that prevents subsequent resin entry. Furthermore, the borate ester bonds are dynamically reversible. When the coating is subjected to external thermal stress or mechanical impact, these bonds can break and reconnect, dissipating strain energy, thus exhibiting extremely impressive cohesive strength and pull-out bond strength (≥1MPa) on a macroscopic scale.

[0023] According to Planck's blackbody radiation law and the law of conservation of energy, for a material to achieve an extreme emissivity >0.98 in the 8–13 μm wavelength range, its real refractive index needs to approach 1 (to reduce Fresnel reflection at the first interface), and its imaginary refractive index (extinction coefficient) must be maximized in this wavelength range. Based on this, this invention constructs a phonon resonant superabsorption / emission cell through component cascading: 1. Aerogel layer: The characteristic peaks of the Si-O-Si asymmetric stretching vibrations of its main porous silica are located at 1050~1150 cm⁻¹. -1 (Corresponding to the 8.7~9.5μm band), the first emission peak is generated.

[0024] 2. Fluorinated graphene: The high density of CF covalent bonds, due to the extremely strong electronegativity difference, produces a very large change in dipole moment, and its strong vibrational absorption band spans 1100~1300 cm⁻¹. -1 (Corresponding to 7.7~9.0μm).

[0025] 3. Strontium titanate core: lattice phonon resonance of Sr-Ti-O and SO4 in hollow BaSO4 2- The deformation vibration of the group just fills the gap in the low-frequency region, filling the gap in the 12~13μm band.

[0026] 4. Fluorosilicone resin: The Si-O-Si bonds in the main chain and the CF bonds in the side chain are supplemented again across the entire frequency band.

[0027] Four distinct phonon vibration modes seamlessly superimpose across the entire 8–13 μm atmospheric window (broadband resonance). Due to the porous nature of the aerogel, the material's macroscopic effective refractive index is as low as approximately 1.1, resulting in minimal interfacial reflection. Thermal energy entering the coating is perfectly captured by these four vibration modes and converted into infrared photons emitted into space, ultimately achieving a physically limit-level vertical emissivity of ≥98%.

[0028] Accordingly, the present invention provides a formulation for an aerogel thermal insulation coating, which, by mass percentage, consists of the following components: Component A: Cis-diol-modified fluorosilicone resin aqueous dispersion, 15-30%; Component B: Hollow BaSO4@SiO2 aerogel microspheres modified with phenylboronic acid, 20-40%; Component C: Praseodymium-doped strontium titanate (Pr-SrTiO3) micro powder, 5-15%; Component D: Fluorinated graphene quantum dots (F-GQDs), 2-8%; Component E: Additives, 2-5%; Component F: Deionized water, replenished to 100%.

[0029] In this aerogel insulation coating, the components work synergistically. Component A, acting as a film-forming agent, undergoes in-situ dynamic covalent cross-linking with the phenylboronic acid groups on the surface of component B through cis-diol groups on its chain segments. This reaction simultaneously achieves two functions: firstly, it forms a cross-linked sealing layer at the pores of the aerogel microspheres in component B, protecting the internal nanopores from being filled by the resin in component A, thus ensuring the material's low thermal conductivity; secondly, it establishes a strong chemical bond interface between the matrix of component A and the filler in component B, imparting high adhesion strength to the coating. Component C, together with the inorganic core (BaSO4) of component B, efficiently reflects sunlight and near-infrared light, blocking external radiative heat input. Component D, in synergy with the main chain of component A, the shell of component B, and the lattice vibrations of component C, constitutes a broadband phonon resonance system, achieving ultra-high infrared emissivity and enhancing passive radiative cooling. Component E ensures the colloidal stability and workability of the system and locks the system pH within the optimal range required for dynamic covalent bond formation. Each component has a clear division of labor and is interdependent, working together to achieve a balance between thermal insulation, high strength, high reflectivity, and extreme emission performance.

[0030] Based on this, the present invention further provides a specific synergistic formulation scheme: In this aerogel insulation coating, components A and B synergistically form a key-lock system between the resin and the aerogel. In traditional systems, the resin (usually >30% content to ensure strength) is drawn into the aerogel during drying due to capillary negative pressure.

[0031] In this invention, the ratio of cis-diol resin (15-30%) to phenylboronic acid aerogel (20-40%) is strictly limited. If the resin content is below 15%, a macroscopic continuous phase cannot be formed even without inclusions in the pores; if it is above 30%, the coating solid content will be too low, and the intrinsic thermal conductivity of the fluorosilicone resin will exhibit an additive effect. An aerogel content below 20% is insufficient to construct an insulating network, while a content above 40% leads to extreme agglomeration.

[0032] Phenylated acid and cis-glycol do not react under acidic and neutral conditions, but in a weakly alkaline environment (pH 8.5–9.5), they undergo an extremely rapid click-chemical reaction, instantly forming cyclic dynamic borate ester bonds. As the coating is applied and begins to form a film with the evaporation of water, the liquid cis-glycol resin immediately comes into contact with the outermost surface of the aerogel microspheres and undergoes reversible cross-linking with the phenylboronic acid on the surface, instantly forming a high-molecular-weight cross-linked sealing network at the pores of the aerogel. Because the cross-linking causes the local viscosity to instantaneously approach infinity, the resin molecules lose their fluidity and thus completely lose their ability to penetrate deep into the pores. Through this precise in-situ sealing, 99% of the nanopores inside the aerogel are perfectly preserved. Simultaneously, this interfacial covalent bonding endows the resin-filler pair with extreme bonding forces, allowing the macroscopic coating to still exhibit a super-strong adhesion of ≥1 MPa even with low resin content, perfectly resolving the paradox of thermal conductivity and strength.

[0033] To further explain, component A in this aerogel insulation coating, a cis-diol-modified fluorosilicone resin aqueous dispersion, specifically serves as the film-forming substance of the coating, providing the matrix strength and substrate adhesion of the coating, and participating in the dynamic covalent cross-linking reaction at the interface through the cis-diol groups in its side chains.

[0034] The cis-diol-modified fluorosilicone resin aqueous dispersion is specifically prepared by hydrosilylation and free radical copolymerization of hydrogen-containing silicone oil, fluorinated acrylate and allyl compounds containing cis-diol groups (such as glycerol monoallyl ether).

[0035] The amount of component A, cis-diol-modified fluorosilicone resin aqueous dispersion, is preferably 15% to 30%.

[0036] To further explain, component B of this aerogel insulation coating, namely hollow BaSO4@SiO2 aerogel microspheres modified with phenylboronic acid, serves as the core insulation filler and optical reflective filler, while providing dynamic crosslinking sites through the phenylboronic acid groups on its surface.

[0037] The hollow BaSO4@SiO2 aerogel microspheres modified with phenylboronic acid have a distinct core-shell structure. The core is a hollow BaSO4 microsphere synthesized by template method, and the outer shell is a silica aerogel layer with a thickness of 50 to 100 nm. The outer surface of the aerogel layer is covalently grafted with p-carboxyphenylboronic acid through a silane coupling agent with a grafting rate of not less than 5 wt%.

[0038] As further explanation, the hollow BaSO4@SiO2 aerogel microspheres modified with phenylboronic acid can be prepared by the following scheme: first, hollow barium sulfate microspheres are synthesized by template method, then a silica aerogel layer with a thickness of 50-100 nm is grown on its surface by in-situ sol-gel method, and finally 4-carboxyphenylboronic acid is grafted onto its outer surface by silane coupling agent to enrich the phenylboronic acid functional groups.

[0039] The amount of the phenylboronic acid-modified hollow BaSO4@SiO2 aerogel microspheres is preferably between 20% and 40%.

[0040] The praseodymium-doped strontium titanate in this aerogel insulation coating serves as a high-refractive-index reflective pigment, primarily used to enhance the reflectivity of near-infrared sunlight and participate in phonon resonance. Traditional TiO2 is abandoned in this invention because its band gap (approximately 3.2 eV) leads to strong absorption of ultraviolet light with wavelengths <400 nm, converting absorbed light energy into heat and reducing overall insulation performance. SrTiO3, with an extremely high refractive index (n=2.4), and BaSO4, which has no ultraviolet absorption, are selected. The hollow BaSO4 core utilizes Mie scattering theory; its hollow structure, along with the outer aerogel and air, forms multiple refractive index interfaces (n(BaSO4) = 1.64, n(SiO2) = 1.46, n(air) = 1.0), significantly enhancing backscattering of sunlight across the entire 0.3~2.5 μm wavelength range. Based on this, by doping rare earth Pr elements into the SrTiO3 lattice, the optical band gap was widened without sacrificing the high refractive index, and an additional local surface plasmon resonance (LSPR) effect was induced, making its reflectivity in the near-infrared band (0.78~2.5μm) reach an astonishing 0.92 or higher, effectively blocking the input of solar radiation heat.

[0041] The praseodymium (Pr) doping molar ratio here is 2 to 5 mol% strontium titanate (SrTiO3) micro powder with a particle size of 200 to 500 nm.

[0042] The preferred dosage of praseodymium-doped strontium titanate is 5-15%. Below 5%, the enhancement effect on near-infrared reflectance and contribution to phonon resonance are not significant. Above 15%, the volumetric cost of the coating increases significantly, and the high-density SrTiO3 particles are prone to sedimentation, affecting the storage stability of the coating. Furthermore, when the Pr doping content is below 2 mol%, the localized surface plasmon resonance effect is not obvious; above 5 mol%, it may introduce excessive lattice defects, leading to enhanced phonon scattering and consequently reducing reflectivity.

[0043] Fluorinated graphene quantum dots in this aerogel insulation coating serve as the core emissivity enhancer. Through their high-density CF bonds, they provide strong characteristic absorption in the 8 to 13 μm infrared window, making them a key component for achieving ≥98% emissivity.

[0044] The emissivity of ordinary polymer coatings is limited by the molecular bond system and is usually only around 0.85. To achieve blackbody-level emissivity of 0.98, an extremely strong, continuous and dense phonon vibration absorption peak must be present in the atmospheric infrared transparency window of 8~13μm (according to Kirchhoff's thermal radiation law, high absorption means high emission).

[0045] This scheme utilizes fluorinated graphene quantum dots (F-GQDs) with a highly dense semi-aromatic topology and extremely high polarizability CF bonds. The stretching vibration frequencies of the CF bonds fall precisely within the range of 1100–1300 cm⁻¹. -1 (Corresponding to approximately 7.7~9μm).

[0046] The content of F-GQD is selected to be 2-8%. If it is too low, a continuous emission network cannot be formed, and if it is too high, the coating color will be deepened and the visible light reflection will be affected.

[0047] The additives in this aerogel insulation coating are used to adjust the coating's pH value, dispersibility, leveling, and defoaming properties, ensuring its workability and storage stability.

[0048] Specifically, the additives include a pH adjuster (AMP-95), a polycarboxylate dispersant, a polyurethane associative leveling agent, and a silicone defoamer. The pH adjuster here is 2-amino-2-methyl-1-propanol.

[0049] The optimal dosage of this additive is 2-5%. If the dosage is below 2%, it cannot effectively perform the aforementioned auxiliary functions; if the dosage is above 5%, the additive, as a small molecule organic compound, will reduce the cohesive strength and water resistance of the coating if introduced in excess. The dosage of 2-amino-2-methyl-1-propanol (AMP-95) needs to be precisely controlled to lock the pH of the system between 8.5 and 9.5, which is a necessary condition for triggering the formation of dynamic borate ester bonds.

[0050] Regarding the formulation scheme of the high-emissivity aerogel thermal insulation coating based on dynamic covalent bond pores and phonon resonance, this invention further provides a corresponding preparation process for the high-emissivity aerogel thermal insulation coating based on dynamic covalent bond pores and phonon resonance. This preparation process mainly includes the following steps: Step (1): Preparation of base solution; In this step, deionized water, polycarboxylate dispersant, and fluorinated graphene quantum dots (F-GQDs) are added to a container in the prescribed amounts. The ultrasonic dispersion equipment is then started, and the mixture is ultrasonically treated for 30 to 60 minutes under ice-water bath conditions to obtain a uniform, non-agglomerated F-GQDs dispersion base solution.

[0051] In this step, ultrasonic dispersion utilizes the cavitation effect to break up any soft aggregates that may exist in the F-GQDs, allowing them to be stably suspended in water at the nanoscale. The dispersant adsorbs onto the surface of the F-GQDs, providing electrostatic or steric stabilization. This step ensures that the building blocks of the subsequent phonon resonance network exist in a monodisperse or oligolayer form, a prerequisite for maximizing its infrared absorption efficiency.

[0052] Step (2): Preparation of filler slurry; In this step, praseodymium-doped strontium titanate (Pr-SrTiO3) micro powder is added to the base liquid obtained in step (1). The mixture is then transferred to a high-speed shear disperser and subjected to high-speed shear dispersion treatment at a speed of 1500 to 3000 r / min for 20 to 40 minutes.

[0053] This step utilizes strong shear force to uniformly disperse micron- or submicron-sized Pr-SrTiO3 powder in the liquid phase, breaking down its initial agglomerates. The shear strength of this step is sufficient to disperse the micron-sized powder without destroying its crystal structure.

[0054] Step (3): Mixing the film-forming materials; This step involves transferring the dispersion slurry obtained in step (2) into a low-speed stirring tank. Under continuous stirring, the cis-glycol-modified fluorosilicone resin aqueous dispersion is slowly added, and the mixture is stirred for 15 to 30 minutes until the system is homogeneous.

[0055] This step initially fuses the film-forming material with the filler slurry, forming the liquid matrix of the coating. Step (4): Introduction of aerogel microspheres; This step involves reducing the stirring speed to a low shear range of 30 to 60 r / min. Under these low shear conditions, the phenylboronic acid-modified hollow BaSO4@SiO2 aerogel microspheres are slowly added in batches, with stirring for 5 to 10 minutes after each batch, until all microspheres are added and thoroughly mixed.

[0056] The microspheres added in this step have a brittle silica aerogel shell, which would break under high shear forces. Using a low-speed, batch-addition method minimizes mechanical damage and ensures that the microspheres' thermal insulation, reflective properties, and chemical cross-linking functions are not compromised.

[0057] Step (5): pH adjustment and defoaming; In this step, AMP-95 is added to the coating mixture obtained in step (4), and the pH value is precisely adjusted to 8.5 to 9.5. Then, leveling agent and defoamer are added, and after stirring evenly, the coating is placed in a vacuum degassing kettle and degassed for 10 to 15 minutes under a negative pressure of -0.09 MPa.

[0058] The addition of AMP-95 establishes an alkaline microenvironment for dynamic covalent bond formation, which is essential for activating the interfacial pore-protection function. Vacuum degassing removes microbubbles introduced during stirring, preventing them from forming defects in the cured coating and affecting coating quality.

[0059] Through the above formulation and process, the coating of the present invention, after coating and curing, will form a coating with a unique multi-level composite structure. Microscopically, the coating consists of a continuous matrix phase composed of cis-diol-based fluorosilicone resin, within which tightly embedded aerogel microspheres retaining their intact nanoporous structure. At the interface between the resin and the aerogel microspheres, chemical bonds are formed through dynamic borate ester bonds. Praseodymium-doped strontium titanate micropowder and fluorinated graphene quantum dots are uniformly dispersed in the resin matrix. The performance characteristics of this coating are: thermal conductivity ≤0.04 W / (m·K); pull-out bond strength to the substrate ≥1.0 MPa; solar reflectance ≥0.9, near-infrared reflectance ≥0.9; vertical emissivity ≥98% in the 8 to 13 μm wavelength band.

[0060] The high-emissivity aerogel insulation coating based on dynamic covalent bond pores and phonon resonance provided by this invention can be widely used in fields with extremely high requirements for insulation, strength, and radiative cooling, such as energy-saving insulation of building exterior walls and roofs, thermal insulation of industrial storage tanks and heating pipe networks, and thermal protection of aerospace vehicle skins. This coating can be applied using conventional methods such as spraying, roller coating, or brushing.

[0061] The technical solution of the present invention will be described in more detail below with reference to specific embodiments and comparative examples. The coatings prepared in each embodiment and comparative example were all coated on aluminum alloy cement substrates of the same specifications, and the cured film thickness was uniformly 1.0 mm. Performance characterization was carried out under the same test standards.

[0062] Testing standards: Thermal conductivity: Refer to GB / T 10294-2008 "Determination of steady-state thermal resistance and related properties of thermal insulation materials - protective hot plate method".

[0063] Bond strength (pull-out method): Refer to JG / T 24-2018 "Synthetic Resin Emulsion Sand-textured Architectural Coatings".

[0064] Solar reflectance and near-infrared reflectance: Measured using an ultraviolet-visible-near-infrared spectrophotometer equipped with an integrating sphere, in accordance with GB / T 25261-2018 "Reflective Thermal Insulation Coatings for Buildings".

[0065] Vertical emissivity (8 to 13 μm band): Measured using a Fourier transform infrared spectrometer (FTIR) and an integrating sphere accessory, in accordance with GJB 2502.2-2006 "Test Methods for Thermal Control Coatings of Spacecraft - Part 2: Thermal Radiation Performance Test".

[0066] (I) Formulations and preparation of the examples and comparative examples Examples 1 to 9: The formulations for Examples 1 to 9 are shown in the table below (total amount is 100%, the remainder is deionized water). In all examples, the pH of the system was strictly adjusted to 9.0 by adding AMP-95 during preparation. The preparation process followed the complete process of steps (1) to (5) above, avoiding vigorous high-pressure grinding throughout the process to protect the microsphere structure.

[0067] Table 1: Formulation Table for Examples 1-9 (mass percentage, %)

[0068] Note: Component E (3%) contains 0.5% polycarboxylate dispersant, 0.5% silicone defoamer, 1.0% polyurethane associative leveling agent, and 1.0% AMP-95 (used to adjust the pH to around 9.0).

[0069] Comparative Examples 1 to 6: The design principles and formulation changes of Comparative Examples 1 to 6 are as follows. Except for the changes specifically pointed out, the other components and preparation steps are consistent with those of Example 1.

[0070] Comparative Example 1 (without dynamic pore-protecting bonds): Component A (cis-diol-modified fluorosilicone resin) was replaced with an equal mass of commercially available pure acrylic resin aqueous dispersion. This resin does not contain cis-diol groups and cannot undergo dynamic crosslinking with component B.

[0071] Comparative Example 2 (Ordinary Aerogel): Component B (phenylboronic acid modified hollow BaSO4@SiO2 aerogel microspheres) was replaced with an equal mass of commercially available unmodified ordinary hydrophobic SiO2 aerogel powder, which does not contain phenylboronic acid groups on its surface and has no hollow core-shell structure.

[0072] Comparative Example 3 (Traditional Reflective Material): Component C (Pr-SrTiO3 micro powder) was replaced with an equal mass of rutile titanium dioxide (TiO2) pigment.

[0073] Comparative Example 4 (without F-GQDs): No D component (F-GQDs) was added at all, and its mass fraction (5%) was made up by deionized water.

[0074] Comparative Example 5 (acidic reaction environment): The same material formulation as in Example 1 was used, but instead of adding AMP-95 in step (5), a small amount of citric acid solution was added to adjust the pH of the system to a slightly acidic environment of 6.0.

[0075] Comparative Example 6 (Commercially Available Products): An aerogel-type reflective heat insulation coating product from a well-known international brand was purchased and compared as an industry benchmark.

[0076] (II) Performance Test Results The coatings prepared in Examples 1 to 9 and Comparative Examples 1 to 6 were subjected to performance tests, and the results are summarized in Table 2.

[0077] Table 2: Summary Table of Test Results for Various Performance Indicators

[0078] (III) Results Analysis (1) Definitive verification of the dynamic covalent bond hole protection mechanism (comparison of Example 1 with Comparative Examples 1, 2, and 5): Comparative Example 1 replaced the resin with ordinary acrylic resin without cis-diol groups, Comparative Example 2 replaced the aerogel with ordinary aerogel without phenylboronic acid groups, and Comparative Example 5 disrupted the alkaline microenvironment required for the formation of borate ester bonds by adjusting the pH to 6.0. All three cases resulted in the inability of in-situ dynamic cross-linking reactions to occur on the surface of the aerogel microspheres. As a result, the thermal conductivity of the three samples soared to 0.068, 0.075, and 0.072 W / (m·K), respectively, more than doubling the 0.031 W / (m·K) of Example 1. This conclusively demonstrates that the dynamic covalent cross-linking reaction of cis-diol-phenylboronic acid at pH 9.0, designed according to the present invention, constitutes the kinetic barrier preventing resin penetration into the aerogel pores. Simultaneously, the bond strength of Comparative Examples 1 and 5 decreased significantly to 0.65 and 0.70 MPa, respectively, indicating that without dynamic covalent bond interfacial anchoring, physical adsorption alone cannot provide sufficient adhesive force at low resin contents. This further highlights the crucial contribution of dynamic cross-linking to mechanical strength.

[0079] (2) Verification of the superiority of the high-reflectivity filler system (comparison of Example 1 and Comparative Example 3): Comparative Example 3 uses traditional rutile TiO2 as the reflective filler. Although its thermal conductivity and bonding strength are comparable to those of Example 1, its solar reflectance and near-infrared reflectance are reduced to 0.85 and 0.81, respectively, both significantly lower than the target threshold of 0.9. This is due to the ultraviolet absorption characteristics of TiO2 and the attenuation of its refractive index in the near-infrared region. This comparison clearly confirms that the "hollow BaSO4@SiO2 core-shell microspheres + Pr-SrTiO3" filler combination used in this invention has significant performance advantages over the traditional TiO2 solution in achieving high reflectance across the entire wavelength range.

[0080] (3) Confirmation of the source of ultra-high emissivity (comparison between Example 1 and Comparative Example 4): Comparative Example 4 removed fluorinated graphene quantum dots (F-GQDs) from its formulation, resulting in a sharp decrease in its vertical emissivity from 98.8% in Example 1 to 92.1%. While 92.1% is already a high value in conventional coatings, it falls far short of the ≥98% threshold. This comparative result irrefutably demonstrates that the high-density CF bonds introduced by F-GQDs, with their phonon vibration absorption peaks, are a crucial piece of the puzzle in completing the entire broadband resonant network in the 8–13 μm band, enabling the coating emissivity to reach blackbody levels.

[0081] (4) Compared with the overall progress of the prior art (compare Example 1 and Comparative Example 6): Comparative Example 6 represents the best commercially available benchmark product. Example 1 surpasses the benchmark product in all five key performance indicators: thermal conductivity (0.031 vs 0.058), bond strength (1.35 vs 0.85), solar reflectance (0.94 vs 0.86), near-infrared reflectance (0.93 vs 0.83), and vertical emissivity (98.8% vs 89.5%). In particular, the nearly 10 percentage point lead in emissivity constitutes a generational technological advantage, fully demonstrating the innovative value and industrial application potential of this invention.

[0082] The systematic comparison of the above embodiments and comparative examples conclusively demonstrates that the present invention successfully constructs an adaptive dynamic interface pore-protection mechanism through in-situ dynamic covalent crosslinking of cis-diol-based fluorosilicone resin and phenylboronic acid-modified aerogel microspheres; and successfully constructs a broadband resonant emission system covering the atmospheric infrared window through seamless splicing of multi-level component phonon vibration absorption peaks. The synergistic effect of these two core innovative mechanisms enables the aerogel thermal insulation coating of the present invention to achieve unification of multiple contradictory performance indicators for the first time, possessing extremely high industrial application value and commercial promotion prospects.

[0083] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A high-emissivity aerogel thermal insulation coating based on dynamic covalent bond pores and phonon resonance, characterized in that, By mass percentage, it contains the following components: 15-30% cis-diol-modified fluorosilicone resin aqueous dispersion; 20-40% phenylboronic acid-modified hollow BaSO4@SiO2 aerogel microspheres; 5-15% praseodymium-doped strontium titanate micropowder; 2-8% fluorinated graphene quantum dots; 2-5% additives; and the balance being deionized water.

2. The aerogel thermal insulation coating according to claim 1, characterized in that, The cis-diol-modified fluorosilicone resin is a polymeric film-forming base material prepared by hydrosilylation and free radical copolymerization of hydrogen-containing silicone oil, fluorinated acrylate and allyl compound containing cis-diol groups.

3. The aerogel thermal insulation coating according to claim 1, characterized in that, The hollow BaSO4@SiO2 aerogel microspheres modified with phenylboronic acid have a distinct core-shell structure. The core is a hollow barium sulfate microsphere, and the outer shell is a silica aerogel layer. The outer surface of the aerogel layer is covalently grafted with p-carboxyphenylboronic acid molecules, with a grafting rate of not less than 5 wt%.

4. The aerogel thermal insulation coating according to claim 1, characterized in that, The praseodymium-doped strontium titanate micropowder has a praseodymium doping molar ratio of 2-5 mol% and a particle size of 200-500 nm.

5. The aerogel thermal insulation coating according to claim 1, characterized in that, The additives include pH adjusters, dispersants, leveling agents, and defoamers.

6. The method for preparing the aerogel thermal insulation coating according to any one of claims 1-5, characterized in that, Includes the following steps: (1) Mix measured amounts of deionized water, dispersant and fluorinated graphene quantum dots, and perform ultrasonic dispersion treatment to obtain a uniform base liquid; (2) Add praseodymium-doped strontium titanate micro powder to the base liquid obtained in step (1) and perform high-speed shear dispersion to obtain a dispersion slurry; (3) Add cis-diol-modified fluorosilicone resin aqueous dispersion to the dispersion slurry obtained in step (2) and stir until homogeneous; (4) Add phenylboronic acid-modified hollow BaSO4@SiO2 aerogel microspheres slowly in batches to the mixture obtained in step (3) under low shear stirring conditions, and mix evenly; (5) Add a pH adjuster to the mixture obtained in step (4) to adjust the pH value of the system to a weakly alkaline range of 8.5 to 9.5, then add a leveling agent and a defoamer, and then perform vacuum degassing treatment to obtain the aerogel thermal insulation coating.